Pengaruh Kemudahan Penggunaan, Reputasi dan Online Trust Terhadap Minat Beli Pada E-Commerce Lazada - Vicy Andriany; Randy Pratama Yuspian (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to determine the influence of the variables Ease of Use (X1), Reputation (X2), and Online Trust (X3) on Purchase Interest on Lazada (Y) partially and simultaneously. The type of research that the author uses is field research with a quantitative approach, namely the method used to research certain populations and samples by collecting data using research instruments with the aim of testing predetermined hypotheses. The research results found that partially the ease of use variable did not have a significant effect on buying interest, the reputation variable had a significant effect on buying interest and the online trust variable had a significant effect on buying interest. Meanwhile, the results of the simultaneous test show that the variables ease of use, reputation, and online trust have a significant effect on buying interest..